Rinosinusitis Kronis dengan Polip Nasal Inflamatori Bilateral serta Elongated Unsinatus - Bestari Jaka Budiman; Dolly Irfandy; Mohd Redza Qurniawan (Jurnal Kesehatan Andalas, 2023)
Chronic rhinosinusitis (CRS) is defined as chronic inflammation of the nose and paranasal sinuses with two or more symptoms, one of which can be nasal congestion/obstruction/congestion or rhinorrhea (anterior/postnasal drip), and/or with facial pain, reduced or loss of smell. Elongated uncinate is one of the anatomical variants of the uncinate process where the uncinate process is curved or bent, which causes sinus problems and is one of the risk factors for CRS. It has been reported a 19-year-old man with the diagnosis of chronic rhinosinusitis with third-grade bilateral nasal polyp from computed tomography of the paranasal sinusitis. There was an impression of the sinonasal polyp with inverted papilloma as a differential diagnosis. The patient was treated through microdebrider-assisted functional endoscopic sinus surgery. This was chronic rhinosinusitis with grade III bilateral nasal polyps, and microdebrider-assisted fungsional endoscopic sinus surgery was performed with great results.Keywords: chronic rhinosinusitis, elongated unsinatus,  functional endoscopic sinus surgery, nasal polyp